2001
DOI: 10.17221/8368-pps
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance to Fusarium oxysporum f.sp. sesami in hybrid lines of sesame (Sesamum indicum L.) under greenhouse conditions

Abstract: Thirty-six samples of sesame (15 F1 and 15 F2 generations and their 6 parents) were evaluated for their reaction to Fusarium oxysporum f.sp. sesami (Zaprometoff) Castellani after artificial inoculation in greenhouse tests. The experimental soil was analysed mechanically and microbiologically. Reactions of the plants were recorded on a scale from 0 = no visible infection (immune) up to 6 = 70% infected plants (highly susceptible). Highly significant differences of susceptibility and resistance to the wilt patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…Such crosses might be helpful for breeding programs due to their stable resistance. Similar findings were reported for the same disease by EL-MARZOKY (1982) and for other diseases by EL-BRAMAWY (2003) and AMMAR et al (2004). In regard to seed yield/feddan, there was little change from F 3 to F 4 as well as from 2004 to 2005.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Such crosses might be helpful for breeding programs due to their stable resistance. Similar findings were reported for the same disease by EL-MARZOKY (1982) and for other diseases by EL-BRAMAWY (2003) and AMMAR et al (2004). In regard to seed yield/feddan, there was little change from F 3 to F 4 as well as from 2004 to 2005.…”
Section: Resultssupporting
confidence: 89%
“…The F 3 's and F 4 's as segregating sesame generations had been produced in a breeding program at the Agronomy Department, Faculty of Agriculture, Suez Canal University, Ismailia, Egypt, concerning, among other characters, the resistance to Fusarium wilt (EL-BRAMAWY 1997, 2003EL-SHAZLY et al 1999;EL-BRAMAWY et al 2001;AMMAR et al 2004 No. a commercial field (Abo Soltan Village, Ismailia Gov.)…”
Section: Methodsmentioning
confidence: 99%
“…The results showed clearly that these segregates could be stable for their reaction to the disease (R or S or HS) through the seasons of evaluation, with some segregation from one generation to the next. This finding is in agreement with previous works (EL-MARZOKY 1982;EL-SHAKHESS 1998;EL-BRAMAWY 2003).…”
Section: Resultssupporting
confidence: 94%
“…Similar results had been reported by some other researchers, e.g. XIAO et al (1992a, b), KUMAR and MISHRA (1992), ZIDAN (1993), RAGHUWANSHI et al (1995a, b), EL-BRAMAWY (1997, 2003, EL-SHAZLY et al (1999), AMMAR et al (2004), who found significant differences among sesame populations under both natural and artificial infection by F. oxysporum f.sp. sesami.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation